PENYULUHAN PENDIDIKAN POLITIK BAGI PEMILIH PEMULA GUNA MENINGKATKAN PARTISIPASI HAK PILIH PADA PEMILIHAN GUBERNUR DKI JAKARTA TAHUN 2017 (Studi pada Siswa-Siswi Sekolah Menengah Atas Se-Kecamatan Tanjung Priok) - Amsori, Amsori (JE (Journal of Empowerment), 2017)
The purpose of this article is to explain the extension activities of political education for voters in order to improve public understanding of voters, in this case represented by the Students of Senior High School in the district of Tanjung Priok. The method used is a qualitative approach. Data analysis techniques in this study using a descriptive model. The conclusion of this article is all parties must be able to support the efforts of the election organizers in terms of improving the quality of electoral processes; Increase voter participation; Improving public confidence in the democratic process; Generating volunteerism and civil society in the elections and democratization agenda.